GEO-DYNAMIC ANALYSIS OF CRYSTALLINE BASEMENT FORMATION FOR THE SOUTH-WESTERN PART OF UKRAINE - DYMYTROV, G.; KOVAL, V. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2005)
Analisis of geo-dynamic events, rifto-genesis conditions and formation of Lower Proterozoic and Riphean-Vendian continental paleorifts at various stages of development for the south-western part of Ukraine and the nothern part of Moldova has been given.Geodynamic environments of the discrete disruptions of the Earth s crust over the formation period of the Lower Proterozoic Nemirovsko-Vorontcovsco-Strashentsky and Traktemirovsko-Yadlovsko-Talnovsco-Frunzovsky paleorifts where intruzions of tholeiite-komatiite lavas were recorded together with hypogene fluids rich with metal and non-metal elements. Geo-dynamic environments of the RipheanVendian Dniester continental paleorift development are being considered in detail. Intersection sites of the Lower Proterozoic paleorift promising for discoveies of ore and non-ore minerals are briefly described.